Autonomic nervous system activity and workplace stressors-A systematic review - Jarczok, Marc N.; Jarczok, Marion; Mauss, Daniel; Koenig, Julian; Li, Jian; Herr, Raphael M.; Thayer, Julian F. (Neuroscience and Biobehavioral Reviews, 2013)
Aim: This systematic review evaluates and summarizes the evidence of the association between psychosocial work environment as indicated by several work-stress models such as Job-Demand-Control (JDC), Effort-Reward-Imbalance (ERI), or Organizational Justice (OJ) and autonomic nervous system (ANS) function as indexed by heart rate variability (HRV). Method: We conducted a systematic literature search following the PRISMA-Statement in eleven databases including Medline, Web of Science and PsycINFO to address medical as well as psychological aspects of the relation between psychosocial work-stress models and HRV. Results: We identified 19 publications with a total of 8382 employees from ten countries reporting data from the years 1976-2008.Overall, nine of all studies report a negative and significant association between vagally-mediated HRV and measures of stress at work, while eight of all studies report a negative and significant association to mixed sympathetic and parasympathetic measures of HRV. Conclusions: This systematic review provides evidence that adverse psychosocial work conditions are negatively associated with ANS function as indexed by HRV. © 2013 Elsevier Ltd.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Employees; Heart rate variability; Psychosocial strain; Psychosocial work environment; Stress; Vagal tone